Clinical and Demographic Features of Vertigo: Findings from the REVERT Registry - Agus, Sam; Benecke, Heike; Thum, Cornelia; Strupp, Michael; Gasteyger, Christoph (Frontiers in Neurology, 2013)
Introduction Despite being a common disease, data on vertigo management in a real-world setting are scarce. Aims To provide information on the vertigo and its management in a real-world setting. Materials and Methods Data were collected from 4,294 patients with vertigo in 13 countries over 28 months via a multi-national, non-interventional observational study (the so-called REVERT registry). Data included medical history and details of anti-vertigo therapy. ‘Clinical global impression’ (CGI) of severity (CGI-S) was assessed at baseline (V1) and then at 6 months follow-up (V2) along with CGI change (CGI-C). All variables were analysed descriptively. Results The majority of patients were female, >40 years of age, and almost half had co-morbid cardiovascular disease. Diagnoses were split into 4 categories: 37.2% ‘other vertigo of peripheral vestibular origin’, 26.9% benign paroxysmal positional vertigo (BPPV), 20.5% ‘peripheral vestibular vertigo of unknown origin’ and 15.4% Menière’s disease (MD). Betahistine was the most commonly prescribed therapy prior to and after enrolment, and was followed by piracetam, ginkgo biloba and diuretics. MD had the highest proportion of betahistine treated patients. Almost half of patients were ‘moderately ill’ at V1 based on CGI-S. At V2, patient distribution moved towards ‘less severe illness’ (91.0% improved).The greatest improvements were in the more severely ill, and those with BPPV or ‘other vertigo of peripheral origin’. Conclusions There was a reduction in illness severity over the course of the study, some of which is likely to be due to pharmacological intervention. Further studies are needed to confirm these results.